Menemukan Kembali Aktivisme: Peran Jejaring Sosial pada Gerakan Sanitasi Charity Water - Pusparani, Indah Gilang (Global: Jurnal Politik Internasional, 2013)
Most sanitation movements in the world are physical, local-based, and limited to several beneficiaries in the near proximity of the sanitation project. Social networking sites, such as web 2.0, Facebook, YouTube, and Twitter, help to contribute to the reinvention of social activism, making sanitation movement more accessible and available for everyone despite of geographical constraint. This paper aims to analyze the role of social networking sites in shaping the character, the strategy, and the scope of sanitation movement charity: water, using the concept of social movement and social networks.This paper concludes that social networking sites contribute in shaping the charity: water movement to be platform-based and simpler to every users and activists in term of the character of movement. It shapes its strategy to be the platform to connect and mobilize people from around the world, making it accessible for international activists and beneficiaries. Social networking sites enable activism to reinvent itself.